Investigation of Lexical Changes and Vocabulary Meanings of Slang in Millennial and Generation Z on Social Media - Sidqi, Muhamad Alif; Handayani, Sri; Rohbiah, Tatu Siti (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
The use of slang has undergone significant changes in line with the development of technology and social media. This article aims to investigate the lexical changes and shifts in meaning of slang vocabulary used by Millennials and Generation Z across various social media platforms. This study employs a literature review method by examining journals, scholarly articles, and other relevant sources that discuss the phenomenon of slang in the digital context. The findings reveal that slang vocabulary has not only expanded quantitatively but also experienced semantic shifts influenced by social, cultural, and digital technological factors. Furthermore, it was found that Millennials and Gen Z tend to create and disseminate new terms rapidly through social media, shaping group identity and user solidarity. This study is expected to contribute to the understanding of language dynamics in the digital era, particularly in the field of sociolinguistics.